Assessment Analysis on P5 Project Based on Local Wisdom in D Phase at MTs Nurul Ilmi Salimpat - Nofembra; Varizki Syaf Putra (KIPS Institute, 2025)
This study aims to determine the purpose of the assessment itself and its impact on students participating in P5 activities outlined in the current new curriculum, with the theme of local wisdom. The development of this activity program is based on project learning. The study involved grade VII at MTS Nurul Ilmi Salimpat in the 2023-2024 academic year. The method used in this study is a qualitative approach with exploratory studies, primary data, and supporting data. The primary data comes from interviews, observations, and documentation studies during the implementation of the activity, while supporting data is obtained from the school curriculum and components determined by the independent curriculum. The findings of the research are then analyzed and presented descriptively and documented. The results of the study show the purpose of the P5 activity assessment, which can provide new values ??for students and teachers. Students can also understand that this is their own culture, their duty to preserve local wisdom (kembang Loyang and pinyaram).